Factors Affecting Perineal Wound Healing in Postpartum Women at Puskesmas X - Ai Desti; Tuti Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: There were 2.7 million cases of perineal lacerations or lesions among birthing mothers worldwide in 2019. This number is projected to reach 6,300,000 by 2050. In Indonesia, 75% of vaginally birthing women encounter perineal lacerations or wounds. 57% of mothers who had spontaneous vaginal births in the year 1951 obtained perineal sutures (28% due to episiotomy and 28% due to spontaneous tears). Objectives: To determine the effect of knowledge, personal hygiene and early mobilization, family environment, and culture on the healing of perineal wounds in postpartum mothers at Puskesmas X in 2022. Methods: The research design utilized a cross-sectional, analytic survey methodology. Cross-sectional methodology. There were as many as 28 postpartum women in this study who suffered perineal injuries. The data technique is incorporated into the SPSS program's univariate statistical calculations.. Results: The results of this study indicate that there are influences of knowledge, personal hygiene, early mobilization, family environment and culture on the healing of perineal wounds in postpartum mothers. With a value of p = 0.005, p = 0.034, p = 0.014, p = 0.001, p = 0.004. Conclusion : Knowledge, personal hygiene, early mobilization, family environment, and culture impact perineal wound healing in health centers in 2022, with a significant relationship.